Stretching technique maximizes range of motion - Cornelius, W. L. (1999)
Normal flexibility or joint range of motion (ROM), an important element of physical well-being, can be referred to as the ability to move one or more joints through a full range of motion without pain or restriction.1,2 Flexibility exercise becomes one of the conduits between ROM and health maintenance. An exercise prescription serves as a way for individuals to improve, maintain, and restore normal levels of flexibility. These programs of flexibility exercise can promote normal joint function and recovery from related soft-tissue injuries.1 Consequently, flexibility restoration is a primary goal in rehabilitation programs.3 One of our body`s primary mechanical features is the ability to move the segmental center of gravity about a joint through a full range of motion at high speeds, such as when throwing or kicking a ball.4 This is possible because most of the mechanical levers of the human body are classified as third-class levers. This means the point-of-force application (muscle insertion) is located between the point of resistance (segmental center of gravity) and the axis of rotation (joint). Considerable research has focused on techniques for gaining and maintaining flexibility and their influence on ROM.5-9,11,15,16 Although conventional stretching techniques have demonstrated increases in range of motion,9,11,25,26 the less frequently used but more effective modified proprioceptive neuromuscular facilitation (PNF) stretching technique provides greater change in ROM. In fact, PNF stretching techniques have been shown to be significantly more effective at increasing ROM than conventional stretching techniques.5-11